Twisting Transhumanism: Some Scope and Limits of Sorgner’s Philosophy (Analele Universității București.Filosofie, 2025)
Acknowledging an ontology of permanent becoming has ethical and epistemological consequences for the presentation of a thought system. Ontological presuppositions have consequences for our understanding and our ways of inhabiting the world. These statements are particularly true when we think of transhumanism. The problem is that when these assumptions are not recognized, the proposals of transhumanism are understood as contradictory. In this sense, we analyze Stefan Lorenz Sorgner’s proposal to “twist” transhumanism in order to understand the difference between classical transhumanism and weak Nietzschean transhumanism or metahumanism. We will show that classical transhumanism, based on enlightened presuppositions, has ethical consequences that are too culturally specific to be shared beyond the global north. We will then point out how the ontology of permanent becoming, through ethical and alethic nihilism, makes it possible to distance oneself from classical transhumanism and open oneself to further dialogue. However, we will conclude by pointing out that Sorgner’s concept of negative freedom is not sufficient to sustain a democratic transhumanism beyond Europe. It will be necessary to expand on positive freedom, for the question remains: what can a cyborg, who does not have the minimum material conditions for self-enhancement, do about it?